Hubungan Perilaku Sedentari terhadap Kejadian Prehipertensi pada Mahasiswa Fisioterapi Fakultas Kedokteran Universitas Udayana - Victoria Anastasia Ananda Putri; Ari Wibawa; Ni Luh Nopi Andayani; Ni Wayan Tianing (Universitas Pahlawan Tuanku Tambusai, 2026)
Technological advancements and lifestyle changes in the modern era have led to a decline in physical activity across various groups of society, along with an increase in time spent working, studying, and engaging in screen-based activities. This phenomenon has given rise to a lifestyle characterized by minimal physical activity, known as a sedentary lifestyle or sedentary behavior. Sedentary behavior has become an inseparable part of students’ lives due to academic demands and digital lifestyle patterns. If these habits are not balanced with adequate physical activity, they may increase the risk of various non-communicable diseases, including hypertension at a young age. This study aimed to determine the relationship between sedentary behavior and the incidence of prehypertension among university students. This study used an observational analytic design with a cross-sectional approach. The participants were 73 students selected through purposive sampling based on predetermined inclusion and exclusion criteria. Sedentary behavior was measured using the Sedentary Behaviour Questionnaire, and prehypertension status was determined by measuring blood pressure using a sphygmomanometer. Data analysis was conducted using the Chi-Square test to determine the relationship between sedentary behavior and the incidence of prehypertension. A total of 25 respondents (34.2%) experienced prehypertension, while 48 respondents (65.8%) did not experience prehypertension. The Chi-Square test results showed no significant relationship between sedentary behavior and the incidence of prehypertension, with a p-value=0.457 (p > 0.05). Therefore, there was no significant relationship between sedentary behavior and the incidence of prehypertension among Physiotherapy students at the Faculty of Medicine, Udayana University.